Structural, morphological and biological assessment of magnetic hydroxyapatite with superior hyperthermia potential for orthopedic applications - Smrithi Saroj; U. Vijayalakshmi (Scientific Reports)
Abstract Hydroxyapatite (HA) is an important constituent of natural bone. The properties of HA can be enhanced with the help of various ionic substitutions in the crystal lattice of HA. Iron (Fe) is a vital element present in bones and teeth. In this study, iron-doped HA was synthesized using a refluxing-based sol-gel route with varying concentrations of iron (1–9 M%). Samples were analyzed using an X-ray diffractometer (XRD), UV–Vis Spectrophotometer, Fourier-transform infrared spectroscopy (FT-IR), vibrating sample magnetometer (VSM) and Scanning Electron Microscope (SEM). The biological assessment was carried out by hemolytic assay, anti-bacterial activity and in-vitro biocompatibility. XRD data confirmed the evolution of the hexagonal HA crystal structure with the reduction in the crystallinity and the crystallite size. All the characteristic bands were confirmed using FT-IR which also further proved the existence of A-type carbonated apatite. The UV–Vis spectra confirmed the reduction in the band gap energies owing to the substitution of iron. The SEM results showed a change in the shape of the samples with increasing iron concentration. The magnetic behavior of samples also altered from diamagnetic to ferromagnetic behavior due to the doping of iron with enhanced heating efficiency. All the samples were found to be hemocompatible. The antibacterial efficacy was found to be higher for E. coli (gram-negative) bacteria compared to S. aureus (gram-positive) bacteria. Moreover, the superior cell viability of MG-63 (osteoblast-like) cells was observed in Fe-doped HA, attributed to MTT assay which revealed the enhanced cell viability of osteoblast-like cells in the Fe-doped HA. These results strongly emphasize the potential of the developed samples for bone regeneration applications.